2015
DOI: 10.18632/oncotarget.4473
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule/ML327 mediated transcriptional de-repression of E-cadherin and inhibition of epithelial-to-mesenchymal transition

Abstract: Transcriptional repression of E-cadherin is a hallmark of Epithelial-to-Mesenchymal Transition (EMT) and is associated with cancer cell invasion and metastasis. Understanding the mechanisms underlying E-cadherin repression during EMT may provide insights into the development of novel targeted therapeutics for cancer. Here, we report on the chemical probe, ML327, which de-represses E-cadherin transcription, partially reverses EMT, and inhibits cancer cell invasiveness and tumor cell migration in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…We have previously reported partial reversal of TGF-β-induced EMT with ML327 (10 μM) in an immortalized mouse mammary epithelial cell line [10]. This EMT reversal was associated with upregulation of E-cadherin, a hallmark of epithelial cell fate, as well as a downregulation of the mesenchymal marker, Vimentin.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously reported partial reversal of TGF-β-induced EMT with ML327 (10 μM) in an immortalized mouse mammary epithelial cell line [10]. This EMT reversal was associated with upregulation of E-cadherin, a hallmark of epithelial cell fate, as well as a downregulation of the mesenchymal marker, Vimentin.…”
Section: Resultsmentioning
confidence: 95%
“…ML327 was synthesized as previously described through the Vanderbilt Institute of Chemical Biology [10]. ML327 was solubilized in DMSO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4C). E-cadherin is one of the epithelial molecular markers that is always downregulated during EMT progression [27,28].…”
Section: Effects Of Fgf18 On the Expression Of Proliferation- Migratmentioning
confidence: 99%
“…We have demonstrated that this compound has a profound effect on the expression of e-cadherin at multiple timepoints at both the protein and mRNA level, and is capable of reversing the EMT phenotype and reducing the invasive potential of SW620 cell lines. 7 Compound 11r possesses an excellent in vitro DMPK profile, albeit with significant differences in data between species. Although the mouse clearance was well in excess of hepatic blood flow, low intrinsic clearance was noted in rat (33.1 mL/min/kg) and neglible instrinsic clearance was noted in human microsomal studies.…”
mentioning
confidence: 99%